1929
DOI: 10.1002/cber.19290620449
|View full text |Cite
|
Sign up to set email alerts
|

Über Benzopolymethylenverbindungen, XIV.: Wärme‐Umlagerung von α‐Arylindenen in β‐Aryl‐indene

Abstract: Gelegentlich der kiirzlichl) von dem einen von uns und E. A n t o n beschriebenensynthese des F l u o r a n t h e n s wiesen wir darauf hin, daB die seinerzeit von Graebe2) erwartete Bildung dieses Kohlenwasserstoffs aus 9 -A t h y lf l u o r e n , die im Sinne der dem Fluoranthen friiher erteilten Formel gut denkbar war, im Sinne seiner von uns endgultig festgelegten Konstitution ausbleiben m d t e . G r a e b e erhielt in der Tat aus 9-Athyl-fluoren a d pyrogenem Wege einen allem Anschein nach mit 9 -M e t h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1930
1930
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Since previous studies had reported that broadband irradiation of 1 gave the phenylindan derivative 10 , we confirmed that 21 was also obtained as the only product from 1 under these conditions. Finally, an authentic sample of 10 was prepared following literature procedures (Figure 2B), 6a, although the spectroscopic properties of the material synthesized in our laboratory were different from those reported for the product obtained in the previous photochemical studies of 1 6a 2 (A) Preparation of isochromenes 1 , 18 , and 19 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Since previous studies had reported that broadband irradiation of 1 gave the phenylindan derivative 10 , we confirmed that 21 was also obtained as the only product from 1 under these conditions. Finally, an authentic sample of 10 was prepared following literature procedures (Figure 2B), 6a, although the spectroscopic properties of the material synthesized in our laboratory were different from those reported for the product obtained in the previous photochemical studies of 1 6a 2 (A) Preparation of isochromenes 1 , 18 , and 19 .…”
Section: Resultsmentioning
confidence: 92%
“…The formation of 21 in our irradiation experiments was therefore unanticipated given the previous work on the photochemistry of isochromenes 1 − 3 6a. In order to rule out the possibility that we were forming, but failing to isolate, 10 in our experiments, we prepared an authentic sample starting from 2-phenylindene using literature procedures. 6a, Comparison of the spectroscopic properties of 10 prepared in our laboratory, however, with those reported in the original broadband irradiation studies revealed a number of differences. First, a broad absorbance centered at 3325 cm -1 in the IR spectrum of authentic 10 , presumably associated with the hydroxyl group, was not reported for the photoproduct formed by broadband irradiation of 1 in the original study .…”
Section: Discussionmentioning
confidence: 95%
“…A number of other -substituted naphthalenes have been found to rearrange to the /3-form on heating (103a). Similarly, 1-phenylindene has been found to rearrange to 2-phenylindene on heating (20,87).…”
Section: Hsc H3c Ch(ch3)2 Ch(ch3)2 S-guaiazulenementioning
confidence: 96%
“…Semmler (174) described about twenty different oils with this behavior, among which were the oils of camomile, yarrow, and cubeb. It was estimated in 1936 (109) that of the 260 essential oils for which descriptions were available, about 20 per cent contain azulenes or azulene precursors. Sabetay (170) devised 1 Present address: Isotope Laboratory, E. R. Squibb & Sons, New Brunswick, New Jersey.…”
Section: Introduction and Nomenclaturementioning
confidence: 99%
“…2-Phenylindene was prepared by the method of Braun and Manz. 26 Crude 2-phenylindan-2-ol prepared from 2-indanone and excess phenylmagnesium bromide in dry THE was refluxed for 3 h in 50 mL of 20% aqueous sulfuric acid, cooled, poured into 50 mL of cool water, and extracted with ether. The combined ether extracts were washed with H20, saturated NaHCOg, and brine, dried (MgS04), and concentrated in vacuo to give reddish crystals.…”
Section: Ha + S ^A" + Hs+ (1)mentioning
confidence: 99%